Reduced Dopamine Response to Amphetamine in Subjects at Ultra-High Risk for Addiction - Casey, Kevin F.; Benkelfat, Chawki; Cherkasova, Mariya V.; Baker, Glen B.; Dagher, Alain; Leyton, Marco (Biological psychiatry (1969), 2014)
Not everyone who tries addictive drugs develops a substance use disorder. One of the best predictors of risk is a family history (FH) of substance use problems. In part, this might reflect perturbed mesolimbic dopamine responses. We measured amphetamine-induced changes in [11C]raclopride binding in 1) high-risk young adults with a multigenerational FH of substance use disorders (n = 16); 2) stimulant drug-naïve healthy control subjects with no known risk factors for addiction (n = 17); and 3) subjects matched to the high-risk group on personal drug use but without a FH of substance use problems (n = 15). Compared with either control group, the high-risk young adults with a multigenerational FH of substance use disorders exhibited smaller [11C]raclopride responses, particularly within the right ventral striatum. Past drug use predicted the dopamine response also, but including it as a covariate increased the group differences. Together, the results suggest that young people at familial high risk for substance use disorders have decreased dopamine responses to an amphetamine challenge, an effect that predates the onset of addiction.